2014
DOI: 10.1017/s0007485314000649
|View full text |Cite
|
Sign up to set email alerts
|

Influence of original host on chemotaxic behaviour and parasitism in Telenomus podisi Ashmead (Hymenoptera: Platygastridae)

Abstract: The egg parasitoid Telenomus podisi is a natural control agent of pentatomids, including Euschistus heros and Tibraca limbativentris, and success of parasitism is dependent upon the parasitoid finding the host. We tested the influence of host egg volatiles and the synthetic sex pheromone (zingiberenol) of T. limbativentris on chemotaxic behaviour of T. podisi, as well as, the impact of the original host on parasitoid selection. We used mated female T. podisi (48 h old) that emerged from the eggs of T. limbativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…The results present here are in accordance with those reported by Tognon et al (2014), who are studying volatiles from egg masses, reporting a high attraction by T. podisi to E. heros eggs. Table 1.…”
Section: Discussionsupporting
confidence: 93%
“…The results present here are in accordance with those reported by Tognon et al (2014), who are studying volatiles from egg masses, reporting a high attraction by T. podisi to E. heros eggs. Table 1.…”
Section: Discussionsupporting
confidence: 93%
“…Em holometábolos, a aquisição de aprendizado está relacionada às alterações do sistema nervoso, que podem ocorrer durante a fase juvenil e persistir na fase adulta (Bjorksten & Hoffman, 1998;Barron & Corbet, 1999;Tognon et al, 2013Tognon et al, , 2014 ou ser desencadeada na fase adulta, após a experiência em novos hospedeiros (Barron, 2001), como observado neste trabalho. Fêmeas de Leptopilina heterotoma Thompson, 1862 (Hymenoptera: Eucoilidae) expostas a larvas do hospedeiro Drosophila subobscura Sturtevant, 1942 (Diptera: Drosophilidae) juntamente com os odores de maçã, cogumelos ou de ambos, também responderam significantemente mais ao odor com o qual tiveram experiência (Vet & Schoonman, 1988).…”
Section: Discussionunclassified
“…When parasitoids are close to the host or have physical contact with it, semi-or non-volatile compounds, such as footprints and egg composition, become important for host final recognition, as well as other physical or visual factors, such as texture, color, and vibratory information (Borges et al, 2003;Aquino et al, 2012) (Figure 1 Telenomus podisi is an egg parasitoid of pentatomid bugs that prefers egg masses of the Neotropical brown stink bug, E. heros, whereas T. basalis shows preference for egg masses of the Southern green stink bug, N. viridula Sujii et al, 2002). Despite this preference, Tognon et al (2014), while studying the influence of original hosts on the chemotaxic behavior and parasitism of T. podisi, observed that when Tibraca limbativentris Stål (Hemiptera: Pentatomidae) was the original host, the females parasitized this species over E. heros, whereas those emerging from E. heros exclusively parasitized E. heros' eggs, suggesting that the original host can exert influence on their choice. It is important to note that the parasitoid's host searching begins with an innate behavior; however, this can be modified by successive exposure to a particular host, which can result in learning behavior during the development of the immature stage, remaining as an olfactory memory in the adult stage (Vet & Dicke, 1992;Tognon et al, 2013).…”
Section: Semiochemicals From Host or Host-associated To Manage Parasimentioning
confidence: 99%
“…agropec. bras., Brasília, v.51, n.5, p.454-464, maio 2016 DOI: 10.1590/S0100-204X2016000500005 volatility, such as cuticular hydrocarbon or volatiles from egg masses and footprints (Borges et al, 2003;Conti et al, 2010;Laumann et al, 2011;Tognon et al, 2014), followed by the final recognition of the host through chemical and physical contact traits, including visual cues (Figure 1).…”
Section: Semiochemicals From Host or Host-associated To Manage Parasimentioning
confidence: 99%